MIR30a suppresses prostate cancer cells by increasing apoptosis and regulation of MMPs - Azhar A. Ameen; Dhamia K.Suker (Genius Journals, 2022)
MiR 30a has important association with a wide range of human cancers in control the main features of tumor cells such as proliferation and invasion, metastasis, clinical prognosis ,and treatment response. In the current study effects of the miR30a in induce apoptosis and regulation expression of Matrix Metalloproteinase (MMP2 and MMP9) in PC3 cell line in comparison to Vero cell line was investigated. The effect of miR30a on cell viability was observed by MTT- assay, to assess morphological changes due to apoptosis, cells have been fluorescently stained with acridine orange and ethidium bromide(AO- EB) and followed by qRT-PCR to reveal the levels of Caspase-8 and MMP2,9 in PC3 and Vero cell lines . The results showed that the viability of transfected cells was reduced significantly when compared to those in paired untreated and negative control treated cells as a result of apoptosis , transfected tumor cells showed more apoptotic and necrosis features compared with normal cells , and necrotic features , this was associated with upregulation of caspase8, and down regulation in the expression levels of MMP2 and MMP9 .These results suggested that the miR30a may have a potential role in cancer suppression and thereby.
Keywords: MiR30a; Prostate cancer; MMP2; MMP9; Caspase8; Apoptosis